Stress Management in Job and its Impact on Employee Performance: A case of the Hotels and Restaurants in Surkhet Valley - Thapa, Yashoda (Journal of Nepalese Management and Research, 2022)
The main objective of this paper was to study the causes of stress on the hotel and restaurant employees in Surkhet valley. In addition to this, it focuses on the techniques of stress management and its impact on employee performance. Descriptive research design was applied in this research and primary data was collected through the questionnaire, which includes the personal interview, mail questionnaire, telephone interview and Google Form. There were 150 respondents. among them 83 were from hotel and 67 were from restaurants. The finding of the study concluded that unhealthy working environment was the primary causes of the stress in hotel and restaurant industry. To overcome such stress majority of the respondents, prefer to listen music and this study also find that there is an inverse relationship between stress and the employee performance.